2010
DOI: 10.1007/s00381-010-1129-7
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary treatment of giant invasive prolactinomas in paediatric age: long-term follow-up in two children

Abstract: Multidisciplinary therapeutic approach for giant prolactinomas in paediatric patients can be an effective treatment; despite the invasiveness of these tumours, the efficacy of this combined treatment can reach a satisfactory control of the disease at long term, assuring a good quality of life as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…The giant tumors we observed looked like craniopharyngiomas (solid, cystic ± calcified) in 25%, but posterior pituitary function was deficient in only one case. In agreement with many authors,[ 28 29 30 31 32 33 34 ] we noted that bone destruction of the surrounding structures mimicking skull base tumors was relatively common. But, as total disappearance of giant prolactinomas takes years, it was difficult for us to know if those pituitary tumors destroying the skull base were eutopic ones or ectopic rising from the clivus.…”
Section: Discussionsupporting
confidence: 93%
“…The giant tumors we observed looked like craniopharyngiomas (solid, cystic ± calcified) in 25%, but posterior pituitary function was deficient in only one case. In agreement with many authors,[ 28 29 30 31 32 33 34 ] we noted that bone destruction of the surrounding structures mimicking skull base tumors was relatively common. But, as total disappearance of giant prolactinomas takes years, it was difficult for us to know if those pituitary tumors destroying the skull base were eutopic ones or ectopic rising from the clivus.…”
Section: Discussionsupporting
confidence: 93%
“…Among 16 cases collected from the literature and fulfilling all definition criteria of a true giant prolactinoma (55,56,72,95,105,106,107,108,109,110,111,112,113,114), there were 15 boys with a mean age of 10.8 years (range: 6-14 years) and a mean tumour diameter of 65 mm (range: 40-99 mm) and only one 14.5-year-old girl (95). These giant tumours may also lead to the same various neurologic complications as in adults, such as blindness and cranial nerve palsies (106), hydrocephalus (56,72), proptosis (56,105,108) or nasopharyngeal symptoms (71,114), and they should be considered in the differential diagnosis of every large and erosive paediatric skull base tumour.…”
Section: Giant Prolactinoma In Childrenmentioning
confidence: 99%
“…To the best of our knowledge, there are two reports that consider more than ten-year long-term clinical outcomes of giant prolactinomas. Fraioli et al utilized multidisciplinary treatment for IGPs in two children and finally reached satisfactory control of the disease with a follow-up period of 13 and 14 years [26]. Fernandes et al reported a giant prolactinoma with 10 years of DA treatment, whose prolactin levels decreased by 96.8% with an effective reduction in tumor size [27].…”
Section: Discussionmentioning
confidence: 99%